Dorsolateral Periaqueductal Grey Matter stimulation modifies laryngeal activity and subglottic pressure in spontaneously breathing anaesthetized rats - González-García, Marta; López-González, Manuel Víctor; Carrillo-Franco, Laura; Casermeiro-García, Claudia; Díaz-Casares, Amelia; Dawid-Milner, Marc Stefan (My University, 2022)
Abduction and adduction of the larynx allow changes in airflow necessary for the vibration of the vocal folds and emission of voice. It is known that stimulation of the Periaqueductal Gray matter (PAG) and nucleus retroambiguus (nRA) produces vocalization (Holstege et al., 1989) and lesions in PAG cause mutism in animals and humans (Esposito et al., 1999). The nRA is the perfect target to turn passive into active expiration modifying the activity of laryngeal motoneurons located in the nucleus ambiguus (Subramanian et al., 2009). We have shown that rostral and ventral pontine structures are involved in changes of laryngeal caliber (Lara et al., 2002). It has been also demonstrated a high expression of FOXP2 protein at mesencephalic and pontine regions (PAG, Parabrachial complex and A5 Region) involved in cardiorespiratory control. FOXP2 is a transcription factor required for brain and lung development and it is closely related to vocalization (Stanic et al., 2018). The aim of this study was to characterize the relations between mesencephalic regions (dlPAG) involved in cardiorespiratory control and their possible role in modulating laryngeal activity and their effects on vocalization.
Keywords: Ratas de laboratorio; Laringe; Subglottic Pressure; Laryngeal Motoneurons; DMH-PeF; dlPAG; Nucleus Ambiguus